PERLINDUNGAN HUKUM TERHADAP KONSUMEN PENGGUNA JASA PERHOTELAN MELALUI E-COMMERCE(KASUS HOTEL OYO) - Mohamad Yoga Pratama (2022)
By using a normative juridical research method (a statutory approach) which is carried out by examining various data sources related to research problems. This study discusses the legal protection of hotel service users through e-commerce, especially the Oyo Hotel. Then it will also discuss the dispute resolution process at the National Consumer Protection Agency (BPKN) regarding complaints of OYO Hotel service users in e-commerce that harm consumers. The background of this writing is that the rapid development of technology and information has led to new innovations in the trading system model, namely modern trade, therefore lodging services are now based on e-commerce. So that it can be found that the legal protection of consumers against hotel service users, especially OYO hotels through consumer e-commerce, OYO hotel service users is not only protected by the Consumer Protection Act no. 8 of 1999 can be protected by Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions and Government Regulation (PP) Number 80 of 2019 concerning Trading Through Electronic Systems. The dispute resolution process is through an out-of-court route by the National Consumer Protection Agency with the stages of application, pre-trial and dispute resolution on the decisions of the parties. Suggestions for the government to supervise the application business in any sector related to its responsibilities because the UUPK is weak and unclear then suggestions for business actors on the OYO side must maintain and improve their performance in application-based lodging or e-commerce and OYO provides an office that serves the interests of consumers 1x24 hours while advice for consumers is to know and read about OYO's policies and information so that there are no disputes.